Risk Factors for Hospitalization or Death Among Adults With Advanced HIV at Enrollment for Care in South Africa: A Secondary Analysis of the TB Fast Track Trial. (9th June 2022) - Calderwood, Claire J; Tlali, Mpho; Karat, Aaron S; Hoffmann, Christopher J; Charalambous, Salome; Johnson, Suzanne; Grant, Alison D; Fielding, Katherine L
Abstract: Background: Individuals with advanced HIV experience high mortality, especially before and during the first months of antiretroviral therapy (ART). We aimed to identify factors, measurable in routine, primary health clinic–based services, associated with the greatest risk of poor outcome. Methods: We included all individuals enrolled in the standard-of-care arm of a cluster-randomized trial (TB Fast Track); adults attending participating health clinics with CD4 ≤150 cells/µL and no recent ART were eligible. Associations between baseline exposures and a composite outcome (hospitalization/death) over 6 months were estimated using multivariable Cox regression. Results: Among 1515 individuals (12 clinics), 56% were female, the median age was 36 years, and the median CD4 count was 70 cells/μL. Within 6 months, 89% started ART. The overall rate of hospitalization/death was 32.5 per 100 person-years (218 outcomes/671 person-years). Lower baseline CD4 count (adjusted hazard ratio [aHR], 2.27 for <50 vs 100–150 cells/µL; 95% CI, 1.57–3.27), lower body mass index (aHR, 2.13 for BMI <17 vs ≥25 kg/m 2 ; 95% CI, 1.31–3.45), presence of tuberculosis-related symptoms (aHR, 1.87 for 3–4 symptoms vs none; 95% CI, 1.20–2.93), detectable urine lipoarabinomannan (aHR, 1.97 for 1+ positivity vs negative; 95% CI, 1.37–2.83), and anemia (aHR, 4.42 for severe anemia [hemoglobin <8 g/dL] vs none; 95% CI, CI 2.38–8.21) were strong independent risk factors for hospitalization/death. Conclusions: Simple measures that can be routinely assessed in primary health care in resource-limited settings identify individuals with advanced HIV at high risk of poor outcomes; these may guide targeted interventions to improve outcomes.